2017
DOI: 10.12809/hkjr1615345
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Preoperative Magnetic Resonance Imaging in Staging Endometrial Cancer: a Five-year Experience

Abstract: Objectives: To evaluate the accuracy of magnetic resonance imaging (MRI) in predicting deep myometrial invasion, cervical stromal invasion, and pelvic lymph node involvement in the preoperative assessment of women with endometrial cancer. Methods: Patients with endometrial cancer, having preoperative MRI available, and hysterectomy performed in a regional hospital in Hong Kong between 1 January 2010 and 31 December 2014 were included. Those treated with neoadjuvant therapy or without staging MRI were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Based on title and abstract, 525 studies were relevant. After full‐text screening, 83 studies, comprising 18,205 patients, were included in the systematic review (supplemental online Appendix 2) . Three studies lacked raw data, and because the authors did not respond after being contacted, these publications were excluded .…”
Section: Resultsmentioning
confidence: 99%
“…Based on title and abstract, 525 studies were relevant. After full‐text screening, 83 studies, comprising 18,205 patients, were included in the systematic review (supplemental online Appendix 2) . Three studies lacked raw data, and because the authors did not respond after being contacted, these publications were excluded .…”
Section: Resultsmentioning
confidence: 99%
“…For the reference standard domain, only 7 studies explicitly stated that pathology results were blinded to MRI findings 18 , 20 , 24 , 26 , 31 , 38 , 41 , the remaining 35 studies lacked information for the reference domain. In relation to the flow and timing domain, twenty-four studies reported an appropriate interval between the MRI and pathological examination 5 , 6 , 8 , 10 , 12 - 16 , 18 - 21 , 23 , 24 , 26 , 30 , 31 , 38 , 39 , 41 , 44 , 45 , 50 , and the remaining 18 studies did not report the interval. All studies applied pathological evaluation of the removed uterus except for one study where the evaluation was not reported 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the risk of bias and the patient selection domain, 14 studies explicitly reported that the patients were consecutive [10,12,13,16,21,23,[25][26][27][28]31,[37][38][39], and the remaining 28 studies only reported the start and end times of patient recruitment [5,6,8,11,14,15,[17][18][19][20]22,24,29,30,[40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Concerning the index test domain, 6 studies did not report that histopathology was blinded from the MRI findings [5,22,23,27,40,45].…”
Section: Quality Assessment and Publication Biasmentioning
confidence: 99%